Thiomer solidification of an ASR bottom ash: Optimization based on compressive strength and the characterization of heavy metal leaching - Son, Jae Hyop (Animo Repository, 2017)
This study examines the function of Thiomer solidification as a novel environment friendly construction material and its immobilization capacity over heavy metals in the automotive shredder residue (ASR) bottom ash. The morphology of the mixture using a field emission-scanning electron microscopy consistently illustrated the effective bonding between Thiomer and sand towards ASR bottom ash due to acting as fillers to reduce the gaps in its surface during Thiomer solidification. A D-optimal mixture design was further utilized in order to evaluate and optimize the parameters of Thiomer (25–35 wt%), ASR bottom ash (30–45 wt%) and sand (30–40 wt%) on the response of compressive strength. Result showed that optimum compressive strength of 55.9 MPa can be attained at 33.6, 36.4 and 30.0 wt% of Thiomer, ASR bottom ash and sand, respectively. The solidified Thiomer specimen showed superior structural strength over ordinary Portland cement concrete at curing time of 1 and 7 days. Furthermore, a mean heavy metal concentrations of 0.055 ppm Cu2+, 0.105 ppm Zn2+, 0.045 ppm Pb2+, 0.078 ppm Cr6+ and 0.002 ppm Cd2+ were achieved at various mixture designs in the heavy metal immobilization which satisfies stringent environmental standards. Thus, the application of Thiomer proves to be a promising construction material that can pose as an alternative over common cement due to promoting high durability and being eco-friendly. © 2017 Elsevier Ltd